Discovery learning in the language-for-translation classroom: corpora as learning aids - Silvia Bernardini (Cadernos de Tradução)
This contribution reviews the idea of discovery learning with corpora, proposed in the 1990s, evaluating its potential and its implications with reference to the education of translators today. The rationale behind this approach to data-driven learning, combining project-based and form-focused instruction within a socio-constructivistically inspired environment, is discussed. Examples are also provided of authentic, open-ended learning experiences, thanks to which students of translation share responsibility over the development of corpora and their consultation, and teachers can abandon the challenging role of omniscient knowledge providers and wear the more honest hat of "learning experts". Adding to the more straightforward uses of corpora in courses that aim to develop thematic, technological and information mining competences – i.e., in which training is offered in the use of corpora as professional aids –, attention is focused on foreign language teaching for translators and on corpora as learning aids, highlighting their potential for the development of the three other European Master's in Translation (EMT) competences (translation service provision, language and intercultural ones).